Food-Grade Liposome-Loaded Delivery Systems: Current Trends and Future Perspectives - Mankan, Erkan; Karakas, Canan Yagmur; Saroglu, Oznur; Mzoughi, Mondher; Sagdic, Osman; Karadag, Ayse (MDPI, 2025)
Liposomes have emerged as versatile carriers in the food industry due to their amphiphilic structure, biocompatibility, and ability to encapsulate both hydrophilic and lipophilic bioactive compounds. They offer promising benefits by enhancing the solubility and bioavailability of food ingredients such as vitamins, polyphenols, carotenoids, peptides, and omega-3 fatty acids. However, liposomes in aqueous form often suffer from poor stability, leakage of encapsulated compounds, and sensitivity to environmental conditions. To address these challenges, hybrid delivery systems have been developed by incorporating liposomes into various solid or semi-solid encapsulation matrices such as nanofibers, particles, cast films, hydrogels, and emulsions. These combinations can offer synergistic advantages, including improved structural integrity, enhanced protection during processing and storage, extended-release profiles under digestive conditions, and versatile applicability across different applications. This review comprehensively discusses liposome structure, preparation methods, and their incorporation into various encapsulation matrices, focusing exclusively on food-grade ingredients. It highlights recent advancements in hybrid liposome-based systems tailored for food applications, with an emphasis on their functional performance and delivery efficiency. Overall, these hybrid systems hold great promise for developing next-generation functional foods with improved health benefits and shelf stability.
Keywords: encapsulation; food-grade ingredients; nutraceuticals; health-oriented food; NANO-LIPOSOMES; FISH-OIL; STABILITY; NANOLIPOSOMES; RELEASE; FILMS; FORTIFICATION; TECHNOLOGY; CHOCOLATE; Food Science & Technology